2017
DOI: 10.1186/s12957-017-1219-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the outcomes between thoracoscopic and laparoscopic esophagectomy via retrosternal and prevertebral lifting paths by the same surgeon

Abstract: BackgroundThe objective of the study is to explore the effects of retrosternal and prevertebral lifting paths of the tubular stomach on postoperative complications of patients undergoing cervical anastomosis in thoracoscopic and laparoscopic esophagectomy.MethodsSixty-three patients were retrospectively analyzed. The patients received thoracoscopic and laparoscopic esophagectomy by the same surgeon. According to the path by which the stomach was lifted upward, the patients were divided into two groups: the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Chest discomfort after eating is due to the particularity of oesophageal cancer surgery. During the operation, a tubular stomach needs to be made, and the stomach is lifted from the abdominal cavity to the chest cavity (Liu et al., 2017 ; Lv et al., 2017 ). Therefore, patients may experience chest tightness and shortness of breath after eating.…”
Section: Discussionmentioning
confidence: 99%
“…Chest discomfort after eating is due to the particularity of oesophageal cancer surgery. During the operation, a tubular stomach needs to be made, and the stomach is lifted from the abdominal cavity to the chest cavity (Liu et al., 2017 ; Lv et al., 2017 ). Therefore, patients may experience chest tightness and shortness of breath after eating.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, due to its higher morbidity rates including pulmonary complication and anastomotic leakage, the ST route has not been a favorable choice and only considered as an altenative when PM route was not available [15,25]. However, recent studies demonstrated that the ST route had comparable safety and e cacy to the PM route, and thus became a frequent approach for reconstruction after MIE in many centers [8,11,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the other hand, gastric conduit placed in the ST route would not be affected by mediastinal recurrence or radiation therapy [8,9]. Moreover, reconstruction through the ST route might help avoid some severe complications such as airway-gastric conduit stula [10], hiatal and para-conduit hernia [11,12], and it might reduce incidences of gastroesophageal re ux [13], and pulmonary complications, particularly pneumonia compared with the PM route [14]. Meanwhile some prior studies showed a lower anastomotic leakage rate using PM route [15][16][17][18], the others revealed similar rates of anastomotic leakage between the two groups [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, given the minimal interference with lung function, RS route represents a preferred choice for the patients particularly with poor pulmonary function. 19 Many patients suffering from esophageal carcinoma were already at later stage of disease by their first clinical presentation. The structure of esophagus in those patients was occupied by the tumor mass that was prone to invasively grow and often caused local recurrence after surgery.…”
Section: Discussionmentioning
confidence: 99%